(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2017)
The objective of this study was to evaluate the quality of water purification system and identify the bacteria this system, predict bacterial adherence according to the hydrophobicity of these microorganisms and of the polypropylene distribution loop for purified water. The assessment of drinking water that supplies the purification system allowed good-quality physical, chemical, and microbiological specifications. The physicochemical specifications of the distributed purified water were approved, but the heterotrophic bacteria count was higher than allowed (>;2 log CFU mL-1).The sanitation of the storage tank with chlorine decreased the number of bacteria adhered to the surface (4.34 cycles log). By sequencing of the 16SrDNA genes, six species of bacteria were identified. The contact angle was determined and polypropylene surface and all bacteria were considered to be hydrophilic, and adhesion was thermodynamically unfavorable. This case study showed the importance of monitoring the water quality in the purified water systems and the importance of sanitization with chemical agents. The count of heterotrophic bacteria on the polypropylene surface was consistent with the predicted thermodynamics results because the number of adhered cells reached approximate values of 5 log CFU cm-2.